Front Cover. Issue 8 (2nd August 2022) - Hu, Yuyao; Liang, Dong; Wang, Jing; Xuan, Yaping; Zhao, Fu; Liu, Jun; Li, Ruxin
Abstract: A virtual HiLo based on edge detection (V‐HiLo‐ED) method is proposed for background removing of imaging. V‐HiLo‐ED is a novel method reconstructs the background‐free image by estimating the foreground, which is different from all the existing popular software algorithms that estimate the background. V‐HiLo‐ED owns a better quality than state‐of‐the‐art softwarebased methods and exhibits almost the same performance, but at faster speed compared with hardware‐based methods. Further details can be found in the article by Yuyao Hu, Dong Liang, Jing Wang, Yaping Xuan, Fu Zhao, Jun Liu, Ruxin Li1 (e202200031 ) Abstract : A virtual HiLo based on edge detection (V‐HiLo‐ED) method is proposed for background removing of imaging. V‐HiLo‐ED is a novel method reconstructs the background‐free image by estimating the foreground, which is different from all the existing popular software algorithms that estimate the background. V‐HiLo‐ED owns a better quality than state‐of‐the‐art softwarebased methods and exhibits almost the same performance, but at faster speed compared with hardware‐based methods. Further details can be found in the article by Yuyao Hu, Dong Liang, Jing Wang, Yaping Xuan, Fu Zhao, Jun Liu, Ruxin Li1 (e202200031 )